T. J. Simonsen Splendid Ghost Moths and Their Allies. A Revision of Australian Abantiades, Oncopera, Aenetus, Archaeoaenetus and Zelotypia (Hepialidae) - A. Vives Moreno (SHILAP, 2020)
Revisión de Publicaciones